Estimation of the need for harmonization of technical demands for vehicles used in transit countries to decrease threats made by the accidents, presented in the selected examples - Olejnik, Krzysztof (Transport, 2008)
The paper shows the need to make harmonization of the technical demands concerning the vehicles used in the traffic. The vehicles moving now on the roads in the transit countries were allowed to be driven according to demands which were milder than the present binding ones. Some rules were changed because the performing technical progress and development of the devices allowed sharpening the demands for the new registered vehicles in order to decrease the number of accidents. It results from the fact that earlier registered vehicles are more susceptible to accidents. The analysis of this problem was presented in 4 selected cases connected with the safety of participants in the traffic. The paper also discusses the need to equip the trucks already used in Poland with the devices of indirect visibility which enable to observe a much bigger area in the neighbourhood of the vehicle. Increase of indirect visibility from the driver’s seat improves the safety system of the participants in the road traffic. Application of the demands of the Directive 2003/97 (which is obligatory for the newly produced vehicles) to the vehicles earlier registered can be done by replacement and installment of the new mirrors which contain the bigger areas. The solution to the problem of the limited visibility at the inclined crossing of roads and enlarged crossing by turn to the left is proposed. First published online: 27 Oct 2010